ISLAM NORMATIF DAN HISTORIS (FAKTUAL): Ziarah Epistemologi Integratif-Interkonektif dalam Pendidikan - Amril Mansur (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
This paper focuses on the discussion of normative and historical (factual) Islam in the context of the integrative-interconnected epistemological pilgrimage in education. This study uses descriptive analytic methods, which explore the concepts offered by scientists, especially by M. Amin Abdullah. This study found that applying integrative-interconnected epistemology by intertwining the three successors: Hadharat an-Nash (Text Culture and Turats), Hadharat al-'Ilm (Science Culture) and Hadharat al-Falasafah (Philosophical-Ethical Culture), which believed to be able to neutralize or at least break the ice between normative Islam and historical Islam, and also the achievements of truth that would be produced would certainly be much closer to a more comprehensive truth than if it were done with just one epistemological category. Islamic education, both as an institution and as a subject or subject, including research and development of Islamic sciences, especially those with an epistemological paradigm, integrative-interconnected, become strategic instruments for expressing the ideals of moral ideals in Islam, then achieving them so that peace is reconciled advise that apart from domination and repressiveness as a tangible form of Islamic character rahmatan li al-'alamin in the social reality of life is increasingly functional.